Physical activity and purpose in life of college students in confinement. - Romero-Ramos, Óscar; Romero-Ramos, Néstor; González Suárez, Arnoldo José; Fernández-Rodríguez, Emilio; Niźnikowski, Tomasz (Federación Española de Docentes de Educación Física, 2023)
Abstract. Social isolation and generalized confinement in many countries has caused a decrease in physical activity (PA) and an increase in levels of stress, anxiety and depression. Purpose in life is part of people's psychological well-being, and having a clear purpose allows them to face adversities. In this sense, the influence of PA on psychological well-being in situations of confinement makes it necessary for educational and governmental entities to study and promote it. The objective of this work has been to evaluate the incidence with a PA intervention program (Move yourself at home) on the purpose in life during a period of mandatory confine- ment due to COVID-19. 360 university students participated divided into three groups, control (Sedentary, Sed), and experimental (group with low physical activity, BAct, and physically active, Act). The experimental groups were conducted on a PA intervention program for 11 weeks, from the beginning to the end of the mandatory confinement. A weekly online questionnaire was collected, recording the level of PA (min / week) and the results of the PIL test (purpose in life). The level of PA decreased significantly at the beginning of the confinement and increased significantly in the flexibilization phases. The intervention program was able to help maintain the PA level in participants. PA has a positive effect on the purpose in life and practicing some physical exercise on a regular basis could be a crucial tool to face a state of mandatory confinement.
La actividad física y el propósito en la vida de estudiantes universitarios en situación de confinamiento.
Keywords: Estudiantes universitarios - Ejercicio físico; Estudiantes universitarios - Efectos de la COVID-19; Health; Sport; Coronavirus; Life purpose; Emotions